2021
DOI: 10.1051/e3sconf/202132402001
|View full text |Cite
|
Sign up to set email alerts
|

The Sedimentation Impact for the Lagoon and Mangrove Stabilization

Abstract: Sedimentation causes land accretion, silting river water, lagoon, and mangrove degradation. The current study aims to analyze the potential and the impact of sedimentation toward the potential of the lagoon and mangrove ecosystem in Segara Anakan Lagoon. The research methods used mapping analysis, total suspended solid analysis (TSS), sedimentation rate analysis, biodiversity analysis, and mangrove covering. The result showed that (1) the value of TSS between 0.25-1,16 g L-1 (2) sediment flux between 6,8 - 257… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 50 publications
0
6
0
2
Order By: Relevance
“…Water salinity is a limiting factor for the stratification of water organism distribution vertically and horizontally. The salinity distribution patterns in mangrove zones were influenced by the movement and mixing processes of water material (Hilmi et al 2021d;Yin et al 2018;Ysebaert et al 2016). The salinity was approximately 0.6-19.6 ppt (good category) according to Government Regulation Number 82 of 2001.…”
Section: The Physical and Chemical Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Water salinity is a limiting factor for the stratification of water organism distribution vertically and horizontally. The salinity distribution patterns in mangrove zones were influenced by the movement and mixing processes of water material (Hilmi et al 2021d;Yin et al 2018;Ysebaert et al 2016). The salinity was approximately 0.6-19.6 ppt (good category) according to Government Regulation Number 82 of 2001.…”
Section: The Physical and Chemical Environmentmentioning
confidence: 99%
“…The EEA in Muara Kali Ijo aims to support the conservation of the mangrove ecosystem as an essential ecosystem in Pantai Ayah, Kebumen, because the mangrove ecosystem has a specific affinity (Hilmi et al 2021e), specific environment (Hilmi et al 2021a(Hilmi et al , 2022bXiong et al 2018), specific habitat (Hilmi 2018;Hilmi et al 2021d;Purnama et al 2022), and specific ecosystem (Cochard 2017;Hilmi et al 2015;Lapolo et al 2018). In addition, the mangrove ecosystem in Muara Kali Ijo also has specific functions to reduce and protect tidal flooding (Hilmi et al 2022a;Marois and Mitsch 2017) and permanent water inundation (Bomer et al 2020), decreasing of coastal disasters (Cooray et al 2021;Nur and Hilmi 2021), decreasing of heavy-metal pollution (Chen et al 2021;Hilmi et al 2017b;Syakti et al 2013;Xin et al 2014;Zhang et al 2019), support carbon conservation (Hilmi 2017a), and support feeding, nursery dan spawning activity (Jones et al 2015;Lapolo et al 2018;Nurhayati et al 2021;Reis et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Mangrove in WP-SAL has specific affinity and adaptation is caused by sedimentation, water inundation, and soil properties (Hilmi et al 2021). Sedimentation is a factor that influences the mangrove adaptation in WP-SAL (Hilmi et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The vulnerability of the mangrove ecosystem in SAL is also influenced by climate change 2,9 Climate change has a high impact on the lagoon and mangrove stabilization, including the decreasing catches of shrimp, crab, and shell catches 10,11 , rapidly influencing for the increasing of human demands and economic growth 12, reducing the ecosystem services 13, blocked shipping lanes, as well as reduced fishermen's income and productivity of silvofishery activity 14,15 . Additionally, climate change causes stunting and death of mangrove vegetation 16 , along with critical land and soil 17,18, species distribution, habitat, fishing ground, and socio-economic impacts 19-23. It also directly impacts oceanography and lagoon stabilization, such as increasing sea tides [24][25][26], sea level rise, tidal and water inundation 27-30, sedimentation, ocean and river current [31][32][33] as well as ocean wave 34,35 . The direct and indricet impact of climate change give high impact for mangrove and lagoon ecosystem in SAL.…”
Section: Introductionmentioning
confidence: 99%
“…However, current ecological conditions and climate change have still threatened the stability and area of mangrove and lagoon ecosystems in SAL. For example, the data from 1978 to 2016 shows that the lagoon has reduced from 4186,45 Ha in 1978 to 1482, 75 Ha in 2016 36. Several studies also reported that the degradation of mangroves in Cilacap and SAL is caused by high sedimentation rates 33,36 , high levels of pollution 5,37,38 and tidal inundation3, anthropogenic factors including logging and conversion 2,39 as well as climate change 2,40,41.…”
Section: Introductionmentioning
confidence: 99%